Nanostructured thermosetting systems modified with poly (isoprene-b-methyl metacrylate) diblock copolymer and polyisoprene grafted carbon nanotubes - Espósito, Leandro Hernan (2013)
Nanostructured thermosetting composites based on an epoxy matrix modified with poly(isoprene-b-methyl methacrylate) (PIb-PMMA) block copolymer were prepared through PI block segregation. Morphological structures were examined by means of atomic microscopy force microscopy. As epoxy/pristine multi-walled carbon nanotubes (MWCNT) systems were found to present big agglomerations, with a very poor dispersion of the nanofiller, epoxy/PI-b-PMMA/MWCNT systems were prepared by using polyisoprene-grafted carbon nanotubes (PI-g-CNT) to enhance compatibility with the matrix and improve dispersion. It was found that the functionalization of MWCNT with grafted polyisoprene was not enough to totally disperse them into the epoxy matrix but an improvement of the dispersion of carbon nanotubes was achieved by nanostructuring epoxy matrix with PI-b-PMMA when compared with epoxy/MWCNT composites without nanostructuring. Nevertheless, some agglomerates were still present and the complete dispersion or confinement of nanotubes into desired domains was not achieved. Thermomechanical properties slightly increase with PI-g-CNT content for nanostructured samples, whereas for nonnanostructured epoxy/PI-g-CNT composites they appeared almost constant and even decreased for the highest nanofiller amount due to the presence of agglomerates. Compression properties slightly decreased with block copolymer content, while remained almost constant with nanofiller amount.